The Setting Up of the Djajapura Centre. West Irian Industrial Vocation Training Scheme. Technical Report No. 1 - International Labour Organisation, Geneva (Switzerland).; International Labour Organisation, Geneva (Switzerland). ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1973)
The Industrial Vocational Training Scheme project resulted from a study made by a United Nations mission which recommended procedures for the development of West Irian. The purpose of the project reported was to assist the government in establishing an industrial vocational training scheme consisting of a training department within the Office of Manpower Affairs in West Irian, and two training centers, one at Djajapura and one at Manokari. The Djajapura Center, though still engaged in the construction of the physical facilities, has offered the first 2-year courses. These have been completed by 60 trainees. The courses offered at the center are in five trades: automotive, machine-shop, electrical, woodworking, and carpentry and building. The major difficulties encountered in the project were a shortage of instructors and a shortage of accommodations. The report also discusses in detail 10 policy recommendations and contains an appendix of lists of staff, international experts, government contributions, summary of expenditures, and areas of origin. (BP)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Building Plans; Construction Needs; Developing Nations; Educational Facilities; Educational Policy; Facility Guidelines; Foreign Countries; Industrial Arts; Industrial Education; Job Training; Labor Force Development; National Programs; Problems; Program Descriptions; Teacher Shortage; Vocational Education; Vocational Training Centers; Djajapura Centre (Indonesia); Indonesia (Irian Barat); Reports, Research